2021
DOI: 10.4314/sokjvs.v19i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treatment with trypanocides on Trypanosoma brucei induced oxidative stress and antioxidant enzyme activities in dogs

Abstract: Oxidative stress and alteration of endogenous antioxidant enzymes play roles in the pathophysiological mechanism of trypanosomosis. The oxidative stress marker: malondialdehyde- MDA and antioxidative stress markers: Serum catalase- CAT, Serum Reduced Glutathione -GSH-Rd and Serum Superoxide dismutase- SOD of Nigerian local dogs (NLD) experimentally infected with Trypanosoma brucei were evaluated after treatments with diminazene aceturate (DA) and isometamidium chloride (IMC). Twenty dogs of age 3 – 4 months we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…(2021) for SOD and GSH, while only MDA at day 35 of T. brucei infection of the dogs had a similar trend with the current study. The reversal of the increasing GSH by the Artemether and Diminazene drugs at day 37 of infection of the goats with Surra was also not observed in the report of Akpa et al (2021) that used Diminazene and Isomethamedium Chloride in the treatment of T. brucei infected canine. The zero mortality reported for the Artemether treated group (Salifu et al, 2021) for caprine surra infection may have suggested the ability of the antimalaria drug to having the ability in lowering the AST, ALT, Albumin, Total protein and GSH when compared to Diminazene treated group that had mortality due to relapse.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…(2021) for SOD and GSH, while only MDA at day 35 of T. brucei infection of the dogs had a similar trend with the current study. The reversal of the increasing GSH by the Artemether and Diminazene drugs at day 37 of infection of the goats with Surra was also not observed in the report of Akpa et al (2021) that used Diminazene and Isomethamedium Chloride in the treatment of T. brucei infected canine. The zero mortality reported for the Artemether treated group (Salifu et al, 2021) for caprine surra infection may have suggested the ability of the antimalaria drug to having the ability in lowering the AST, ALT, Albumin, Total protein and GSH when compared to Diminazene treated group that had mortality due to relapse.…”
Section: Resultsmentioning
confidence: 75%
“…Enzymes such as aspartate amino transferase (AST) and alanine amino transferase (ALT) levels are raised (Sharma et al, 2022). Oxidative stress and alteration of antioxidant enzymes have shown some level of correlation to diseases such as trypanosomiasis (Akpa et al, 2021). The quantification of serum concentrations of oxidative stress markers such as Malondialdehyde (MDA), Glutathione-S-Transferase (GSH) and Super Oxide Dismutase (SOD) and antioxidant enzymes also facilitates detection of diseases in mammals (Winter et al, 2009).…”
Section: Introductionmentioning
confidence: 99%